A personal narrative on responding to the tragedy at Pulse in Orlando: A volunteer supervisor's perspective. Issue 1 (2nd January 2018) - Super, John T.
ABSTRACT: In the aftermath of the massacre at Pulse in Orlando, Florida, the helping professions united to help meet the counseling needs created by the traumatic event. This article is a first-person account of a supervisor working with more than 600 volunteer professional helpers who helped the victims, families, friends, and others impacted by the massacre. An event like this elicits both personal and professional responses and, in working with the helpers, the two responses both impacted the work that was done by the supervisor. This account provides a better understanding of skills and dispositions helpful in responding to a community trauma and the personal impact on the supervisor.